SOCIAL CAPITAL AND ORGANISATIONAL COMMITMENT AT HIGHER EDUCATION INSTITUTIONS - Siew Hwa Yen; James K. Campbell; Agus Irianto; Zulyusri; Muhyiatul Fadilah (Asian Academy of Management Journal, 2014)
This study compares the extent of the influence of non-tangible forms of social capital on organisational commitment at Universiti Sains Malaysia (USM), in Penang, Malaysia and two universities in Sumatra, Indonesia, which are, Universitas Andalas and Padang State University. In this study, Universitas Andalas and Padang State University will be represented by APU. Amongst the academic staff at USM, three social capital factors—collective action and shared values, relational trust and cooperation, and cohesive bonds and connectivity through participation—have a strong positive impact on affective and normative commitments. At APU, only the factor of cohesive bonds and connectivity contributes to affective commitment. Collective action and shared values as well as cohesive bonds and connectivity were shown to have contributed to higher normative commitment. Relational trust and cooperation, which are important indicators of social capital, did not seem to have any impact on the three organisational commitments. At USM, continuance commitment was negatively related to cohesive bonds and was not related to any other predictive variables. At APU, higher collective action and shared values reduced continuance commitment.